2022
DOI: 10.1038/s41467-022-34449-5
|View full text |Cite
|
Sign up to set email alerts
|

Intensive grassland management disrupts below-ground multi-trophic resource transfer in response to drought

Abstract: Modification of soil food webs by land management may alter the response of ecosystem processes to climate extremes, but empirical support is limited and the mechanisms involved remain unclear. Here we quantify how grassland management modifies the transfer of recent photosynthates and soil nitrogen through plants and soil food webs during a post-drought period in a controlled field experiment, using in situ 13C and 15N pulse-labelling in intensively and extensively managed fields. We show that intensive manag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 81 publications
0
11
0
Order By: Relevance
“…Previous studies have found that drought reduces C uptake, below‐ground C allocation and soil respiration (Chomel et al, 2019, 2022; Fuchslueger et al, 2014; Ingrisch et al, 2020; Karlowsky, Augusti, Ingrisch, Hasibeder, et al, 2018). Our study suggests that the extent to which such reductions occur depends on drought intensity (Figure 2).…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have found that drought reduces C uptake, below‐ground C allocation and soil respiration (Chomel et al, 2019, 2022; Fuchslueger et al, 2014; Ingrisch et al, 2020; Karlowsky, Augusti, Ingrisch, Hasibeder, et al, 2018). Our study suggests that the extent to which such reductions occur depends on drought intensity (Figure 2).…”
Section: Discussionmentioning
confidence: 96%
“…The researchers showed that the industrial system of intensive grazing management using chemicals and high stocking densities per hectare decreased plant carbon capture and its transfer through soil food webs and soil respiration components compared to extensive management. (Chomel et al 2022) They stated that; "…there is growing awareness of the importance of rhizodeposition as a driver of below-ground energy flow and the structure and functions of soil food webs. "…”
Section: Soil Carbon Sequestration (Scs) As a Cdr Technologymentioning
confidence: 99%
“…"Baseline scenarios, those without additional mitigation, result in global mean surface temperature increases in 2100 from 3.7 °C to 4. 8 °C compared to pre-industrial levels." (IPCCC 2014) According to the IPCC: "Mitigation scenarios in which it is likely that the temperature change caused by anthropogenic GHG emissions can be kept to less than 2 °C relative to preindustrial levels are characterized by atmospheric concentrations in 2100 of about 450 ppm CO2eq (high confidence)….…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, while the global concept of sustainability continues to spread, irrational structural configurations of grasslands (unreasonable cropping patterns and unscientific pasture management, such as planting density, species or grazing methods, etc.) continue to exist, which not only undermines the gains of ecological restoration and conservation, but also exacerbates the conflict between ecological conservation and economic development [ 11 ]. In particular, large-scale cultivation-based rangelands generally have a single planting structure, low biodiversity, high vulnerability and low stability, making it difficult to create a cascade of ecosystem service benefits [ 12 ].…”
Section: Introductionmentioning
confidence: 99%